Losing the Warning Signal: Drought Compromises the Cross-Talk of Signaling Molecules in Quercus ilex Exposed to Ozone - Cotrozzi, Lorenzo; Pellegrini, Elisa; Guidi, Lucia; Landi, Marco; Lorenzini, Giacomo; Massai, Rossano; Remorini, Damiano; Tonelli, Mariagrazia; Trivellini, Alice; Vernieri, Paolo; Nali, Cristina (Frontiers in Plant Science, 2017)
Understanding the interactions between drought and acute ozone (O3) stress in terms of signalling molecules and cell death would improve the predictions of plant responses to climate change. The aim was to investigate whether drought stress influences the responses of plants to acute episodes of O3 exposure. In this study, the behaviour of 84 Mediterranean evergreen Quercus ilex plants was evaluated in terms of cross-talk responses among signalling molecules. Half of the sample was subjected to drought (20% of the effective daily evapotranspiration, for 15 days) and was later exposed to an acute O3 exposure (200 nL L-1 for 5 h). First, our results indicate that in well-water conditions, O3 induced a signalling pathway specific to O3-sensitive behaviour. Second, different trends and consequently different roles of phytohormones and signalling molecules (ethylene, ET; abscisic acid, ABA; salycilic acid, SA and jasmonic acid, JA) were observed in relation to water stress and O3. A spatial and functional correlation between these signalling moleculeswas observed in modulating O3-induced responses in well-watered plants. In contrast, in drought-stressed plants, these compounds were not involved either in O3-induced signalling mechanisms or in leaf senescence (a response observed in water-stressed plants before the O3-exposure). Third, these differences were ascribable to the fact that in drought conditions, most defence processes induced by O3 were compromised and/or altered. Our results highlight how Q. ilex plants suffering from water deprivation respond differently to an acute O3 episode compared to well-watered plants, and suggest new effect to be considered in plant responses to environmental changes. This poses the serious question as to whether or not multiple high-magnitude O3 events (as predicted) can change these cross-talk responses, thus opening it up possible further investigations.